2021
DOI: 10.11646/zootaxa.4993.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Three new Nearctic genera of oak cynipid gall wasps (Hymenoptera: Cynipidae: Cynipini): Burnettweldia Pujade-Villar, Melika & Nicholls, Nichollsiella Melika, Pujade-Villar & Stone, Disholandricus Melika, Pujade-Villar & Nicholls; and re-establishment of the genus Paracraspis Weld

Abstract: We describe three new genera of cynipid oak gall wasps from the Nearctic: Burnettweldia Pujade-Villar, Melika & Nicholls, gen. nov., Nichollsiella Melika, Pujade-Villar & Stone, gen. nov., and Disholandricus Melika, Pujade-Villar & Nicholls, gen. nov. (Hymenoptera: Cynipidae: Cynipini). Burnettweldia includes five species, B. californicordazi Cuesta-Porta, Melika & Pujade-Villar, sp. nov., B. conalis (Weld), comb. nov., B. corallina (Bassett), comb. nov., B. plumbella (Kinsey), comb. nov., B. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…As in several previous phylogenetic treatments of the Cynipini (Rokas et al 2003, Ács et al 2010, Ronquist et al 2015, Cooke 2018, Andersen et al 2021, Brandão-Dias et al 2022), several gall wasp genera, including Andricus, Callirhytis, Neuroterus , and Dryocosmus , were found to be either para- or polyphyletic in our tree topologies (Figures 1–4). Of the genera represented in the tree by more than three species, only three genera: Amphibolips, Acraspis , and Disholcaspis maintain monophyly, the latter only because of a recent revision (Melika et al 2021a) after Cooke (2018) had found Disholcaspis to be polyphyletic. Similarly, some species previously given different names were sufficiently similar such that they likely represent the alternate generations of the same species (Supplemental File 2; Supplementary trees 1–3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As in several previous phylogenetic treatments of the Cynipini (Rokas et al 2003, Ács et al 2010, Ronquist et al 2015, Cooke 2018, Andersen et al 2021, Brandão-Dias et al 2022), several gall wasp genera, including Andricus, Callirhytis, Neuroterus , and Dryocosmus , were found to be either para- or polyphyletic in our tree topologies (Figures 1–4). Of the genera represented in the tree by more than three species, only three genera: Amphibolips, Acraspis , and Disholcaspis maintain monophyly, the latter only because of a recent revision (Melika et al 2021a) after Cooke (2018) had found Disholcaspis to be polyphyletic. Similarly, some species previously given different names were sufficiently similar such that they likely represent the alternate generations of the same species (Supplemental File 2; Supplementary trees 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…Gall wasps were initially identified to species based on the morphological characteristics of the galls from which they emerged, and by their tree host following a variety of resources (Weld and von Dalla Torre 1952, Weld 1957, 1959, 1960, Melika & Abrahamson 2002, Russo 2021, “Gallformers.org” 2021). Though gall morphology was our primary indicator of gall wasp species identity, the assumed wasp genus was verified morphologically from reared wasps against keys (Weld and von Dalla Torre 1952, Zimmerman 2018, Melika et al 2021a) and all wasps selected for sequencing were photographed (see below) such that their identity could be confirmed as needed. We refer to some gall wasps reared from as-yet-undescribed galls by their description on gallformers.org as of December 2021, which includes the best-attempt genus name, followed by the host tree from which that gall was first recorded, and a description of its morphology (e.g., “Callirhytis_q_stellata_pentagonal_cluster”).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations